Downloads in Sports and Their Effects on the Body of Athletes - Mushtariy Razzakova (Genius Publishing Group, 2022)
In this material, the training of qualified athletes in the process of many years of sports training, the development of physical qualities and technical skills specific to the characteristics of each sport, mainly the content of these loads, individually in their own direction. pages of analytical data to dependent observers.
Keywords: training of athletes; physical qualities; technical and tactical skills; material